Hb Knossos (HBB: c.82G > T), β-globin CD 5 (−CT) (HBB: c.17_18delCT) and δ-globin CD 59 (−a) (HBD: c.179delA) mutations in a Syrian patient with β-thalassemia intermedia - Faten Moassas (BMC Pediatrics, 2019)
Abstract Background Beta thalassemia (β-thal) is an inherited hemoglobin disorder characterized by reduced synthesis of the hemoglobin that results in microcytic hypochromic anemia. β-Thalassemia intermedia (TI) is a clinical term of intermediate gravity between the carrier state and β-thalassemia major (β -TM). Case presentation We describe a 12-year-old male proband originating from Al-Quneitra province - southwest Syria. Hematological investigations revealed, pallor and anemia (Hb 9 g/dl). The mean cell volume (MCV) 64 fL; mean cell hemoglobin (MCH) 21.8 pg. Capillary electrophoresis (CE) electropherogram revealed low level of Hb A1 (36.2%), high level of Hb F (62.2%) and low level of Hb A2 (1.6%). The proband requires blood transfusion occasionally. Direct DNA sequencing and Polymerase chain reaction-restriction fragment length polymorphism (PCR/RFLP) for mutations detection were used. The molecular analysis revealed the presence of rare β+ Hb Knossos codon 27 (G > T) (HBB: c.82G > T) variant associated with β0 codon 5 [−CT] (HBB: c.17_18delCT) mutation in beta-globin (β-globin) gene and δ0 codon 59 [−A] (HBD: c.179delA) mutation in delta-globin (δ-globin) gene. The proband tested negative for the common deletional forms of alpha thalassemia (α-thal). Polymorphism of the Xmn-I locus (HBG2: c.-211C > T) revealed that the proband had a homozygous [TT] for Xmn-1 locus. Conclusions To our knowledge, this is the first report of beta thalassemia intermedia due to combination of Hb Knossos /codon 5 [−CT] associated with δ0 codon 59 [−A] in Syrian patient. On the other hand, in Syria, β-thal carriers who have low level of Hb A2 due to decreased δ-chain production, different δ-thal gene mutations must be screened to avoid the failure diagnosis of β-thal disease.